Effects of nursing intervention based on the theory of planned behavior on visual function, blood sugar levels, and quality of life in perioperative patients with diabetic retinopathy - Wang, Fang; Shang, Mengying; Yang, Lin; Jiang, Jing; Huang, Hailian (Frontiers in Medicine, 2025)
ObjectiveTo explore the impact of nursing intervention based on the Theory of Planned Behavior (TPB) on perioperative patients with diabetic retinopathy (DR).MethodsOne hundred and twenty patients with DR admitted to our hospital from January 2021 to January 2024 were divided into intervention group and control group. The control group received conventional nursing intervention. The intervention group received nursing intervention based on TPB. The visual function, blood sugar levels, incidence of adverse events, self-management ability and quality of life of the two groups were compared using t-test or χ2 test.ResultsAfter 2 months of intervention, the peripheral vision score of the intervention group was 5.81 points lower than that before the intervention (P < 0.001); the score of sensory adaptation was 9.20 points lower than that before the intervention (P < 0.001); the score of daily activity restriction was 9.06 points lower than that before the intervention (P < 0.001). After 2 months of intervention, the peripheral vision score in the control group was 1.51 points lower than that before the intervention (P < 0.001); the score of sensory adaptation was 5.20 points lower than that before the intervention (P < 0.001); the score of daily activity restriction was 5.04 points lower than that before the intervention (P < 0.001). Compared with the control group, the intervention group had lower scores on the visual function scale in terms of peripheral vision, sensory adaptation, and daily activity restriction 2 months after the intervention. Specifically, the peripheral vision score of the intervention group was 2.15 points lower than that of the control group (P < 0.001); the sensory adaptation score was 3.97 points lower than that of the control group (P < 0.001); the score of daily activity restriction was 4.00 points lower than that of the control group (P < 0.001). After 2 months of intervention, the fasting blood glucose levels of the intervention group were 3.07 mmol/L lower than those before the intervention (P < 0.001); the 2 h postprandial blood glucose levels were 4.22 mmol/L lower than those before the intervention (P < 0.001); the glycosylated hemoglobin was 3.78% lower than that before the intervention (P < 0.001). After 2 months of intervention, the fasting blood glucose levels of the control group were 1.00 mmol/L lower than those before the intervention (P < 0.001); the 2 h postprandial blood glucose levels were 2.19 mmol/L lower than those before the intervention (P < 0.001); the glycosylated hemoglobin was lower 1.76% than that before the intervention (P < 0.001). Compared with the control group, the intervention group had lower fasting blood glucose levels, 2 h postprandial blood glucose levels, and glycosylated hemoglobin 2 months after the intervention. Specifically, the fasting blood glucose levels of the intervention group were 1.93 mmol/L lower than those of the control group (P < 0.001); the 2 h postprandial blood glucose levels were 2.00 mmol/L lower than those of the control group (P < 0.001); the glycosylated hemoglobin was 1.99% lower than that of the control group (P < 0.001). The incidence of adverse events in the intervention group was 5.01%, and that in the control group was 16.67%. Compared to the control group, the intervention group had a lower incidence of adverse events, with significant difference (P = 0.039). After 2 months of intervention, the self-concept score of the intervention group was 4.70 points higher than that before the intervention (P < 0.001); the score of self-care responsibility was 5.40 points higher than that before the intervention (P < 0.001); the score of self-care ability was 6.34 points higher than that before the intervention (P < 0.001); the score of health knowledge level was 6.36 points higher than that before the intervention (P < 0.001); the total score was 15.00 points higher than that before the intervention (P < 0.001). After 2 months of intervention, the self-concept score of the control group was 2.50 points higher than that before the intervention (P < 0.001); the score of self-care responsibility was 2.16 points higher than that before the intervention (P < 0.001); the score of self-care ability was 3.98 points higher than that before the intervention (P < 0.001); the score of health knowledge level was 3.24 points higher than that before the intervention (P < 0.001); the total score was 8.00 points higher than that before the intervention (P < 0.001). Compared with the control group, the intervention group had higher scores on the ESCA scores of the two groups in the aspects of self-concept, self-care responsibility, self-care ability, health knowledge level and total score 2 months after the intervention. Specifically, the self-concept score of the intervention group was 2.00 points higher than that of the control group (P < 0.001); the self-care responsibility score of the intervention group was 3.22 points higher than that of the control group (P < 0.001); the self-care ability score was 2.30 points higher than that of the control group (P < 0.001); the health knowledge level score was 3.10 points higher than that of the control group (P < 0.001); the total score was 6.00 points higher than that of the control group (P < 0.001). After 2 months of intervention, the reading and fine motor score of the intervention group was 10.11 points higher than that before the intervention (P < 0.001); the score of adjustment ability was 7.16 points higher than that before the intervention (P < 0.001); the score of daily living was 6.57 points higher than that before the intervention (P < 0.001); the score of far vision, movement and light sense was 21.80 points higher than that before the intervention (P < 0.001). After 2 months of intervention, the reading and fine motor score of the control group was 4.71 points higher than that before the intervention (P < 0.001); the score of adjustment ability was 4.38 points higher than that before the intervention (P < 0.001); the score of daily living was 1.81 points higher than that before the intervention (P < 0.001); the score of far vision, movement and light sense was 13.74 points higher than that before the intervention (P < 0.001). Compared with the control group, the intervention group had higher scores on the higher LVQOL scores in the aspects of reading and fine motor, adjustment ability, daily living, and far vision, movement and light sense 2 months after the intervention. Specifically, the reading and fine motor score of the intervention group was 5.33 points higher than that of the control group (P < 0.001); the adjustment ability score was 2.75 points higher than that of the control group (P < 0.001); the daily living score was 4.73 points higher than that of the control group (P < 0.001); the far vision, movement and light sense score was 8.10 points higher than that of the control group (P < 0.001).ConclusionNursing intervention based on TPB can effectively improve the blood glucose control effect of DR patients, improve their visual function, and enhance their self-management ability.